Innovation ambidexterity in Indonesian professional services industry: the role of customer trust and co-creation - Elvia Afkar; Mohammad Hamsal (Cogent Business & Management, 2024)
Professional services firms play a vital role in driving innovation and facilitating growth in various industries. Despite their potential, the professional services industry faces challenges in maintaining innovation maturity. While the innovation concept is widely researched, studies on the factors influencing innovation ambidexterity in the professional services industry are still lacking. This research aims to provide an empirical study on the factors influencing the innovation ambidexterity in these firms, especially on the role of customer trust and co-creation. This quantitative research was carried out through a structured survey instrument and used a convenience sampling technique. Data collected from 104 Indonesian professional industry employees were analysed using a structural equation model (SEM) with SmartPLS4 software version 4.1.0.0. This study concludes that customer trust is a key resource for conducting co-creation. Both customer trust and co-creation have direct impacts towards innovation ambidexterity, which in turn influences business performance. This study advances Dynamic Capabilities Theory with its insights, while managerial implications for companies, and suggestions for future research are also described.
Keywords: 650; Customer trust; co-creation; innovation ambidexterity; professional services industry; dynamic capabilities theory